2023
DOI: 10.1007/s00167-023-07432-w
|View full text |Cite
|
Sign up to set email alerts
|

The “Bankart knee”: high‐grade impression fractures of the posterolateral tibial plateau lead to increased translational and anterolateral rotational instability of the ACL‐deficient knee

Danko Dan Milinkovic,
Christoph Kittl,
Elmar Herbst
et al.

Abstract: Purpose The aim of this biomechanical cadaver study was to evaluate the effects of high-grade posterolateral tibia plateau fractures on the kinematics of anterior cruciate ligament (ACL)-deficient joints; it was hypothesized that, owing to the loss of the integrity of the osseous support of the posterior horn of the lateral meniscus (PHLM), these fractures would influence the biomechanical function of the lateral meniscus (LM) and consequently lead to an increase in anterior translational and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“… 2 , 17 , 33 Although there is no consensus on the role of knee ligament and meniscus in the management of PTPFs, joint instability has been found in certain PTPFs in cases of knee ligament and meniscal injuries. 4 , 18 A few researchers have suggested that knee ligament and meniscal injuries should be considered as one of the key determinants when selecting therapeutic strategies for PTPFs. 17 , 33 Thus, investigations on associated knee ligament and meniscal injuries in PTPFs can assist surgeons in gaining a complete picture of the overall injury, thereby helping develop holistic solutions for these injuries.…”
mentioning
confidence: 99%
“… 2 , 17 , 33 Although there is no consensus on the role of knee ligament and meniscus in the management of PTPFs, joint instability has been found in certain PTPFs in cases of knee ligament and meniscal injuries. 4 , 18 A few researchers have suggested that knee ligament and meniscal injuries should be considered as one of the key determinants when selecting therapeutic strategies for PTPFs. 17 , 33 Thus, investigations on associated knee ligament and meniscal injuries in PTPFs can assist surgeons in gaining a complete picture of the overall injury, thereby helping develop holistic solutions for these injuries.…”
mentioning
confidence: 99%